Pengaruh Konfigurasi Balkon Terhadap Performa Kinerja Ventilasi Alami Dalam Ruangan Pada Bangunan Rusunawa Di Indonesia - Bagus Surya Ananta; Jatmika Adi Suryabrata (Arsir: Jurnal Arsitektur, 2024)
The increase in urbanization has an impact on indoor environmental quality and energy consumption in urban buildings in Indonesia, particularly in low-cost apartment buildings (Rusunawa). Despite providing affordable housing, Rusunawa faces challenges related to electricity consumption in achieving indoor comfort. The implementation of passive design elements such as balconies is expected to maximize natural ventilation indoors. This research aims to identify the influence of balcony configurations on the performance of natural ventilation in Rusunawa buildings in Indonesia, aiming to provide guidance in optimizing indoor comfort through natural ventilation. The method employed in this research is Computational Fluid Dynamics (CFD) simulation using Rhinoceros & Butterfly. The results of the study indicate that the width and depth configurations of balconies significantly enhance the Air Changes per Hour (ACH) and wind speed. A balcony width configuration of 40% yields an indoor air quality improvement of 18-26%, while a depth configuration of 20% results in a 9-10% enhancement